Pemilihan Ulang dan Kepastian Hukum dalam Pilkada: Analisis Putusan Mahkamah Konstitusi Nomor 55/PHPU.BUP-XXIII/2025 - Ahaya, Siska; Moonti, Roy Marthen; Ahmad, Ibrahim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Constitutional Court (MK) Decision Number 55/PHPU.BUP-XXIII/2025 is an important precedent in the dynamics of regional head election law in Indonesia. The Constitutional Court canceled the participation of the North Gorontalo Regent candidate pair because one of the candidates was still undergoing a criminal probation period. This article analyzes the Constitutional Court's legal considerations and their implications for the principle of legal certainty and protection of voters' constitutional rights. This study uses a normative legal approach with a descriptive-qualitative analysis method of laws and regulations and Supreme Court decisions. The results show that the enforcement of strict nomination requirements by the Constitutional Court emphasizes the importance of compliance with the law in the democratic process, while ensuring that regional head candidates have proper moral and legal integrity, this decision also emphasizes that the election process is not only procedural, but also substantial in ensuring the quality of leadership that will be elected. In addition, this decision provides guidelines for election organizers, especially the General Election Commission (KPU), to be more careful in conducting factual verification of candidate requirements. On the other hand, political parties are encouraged to be more selective in nominating candidates, in order to avoid potential legal disputes that could harm public trust in democracy.